Application of the Willis Covered Stent in the treatment of intracranial unruptured aneurysms in internal carotid artery: A retrospective single-center experience. (August 2020) - Yan, Peng; Zhang, Yupeng; Ma, Chao; Liang, Fei; Zhu, Haoyu; Jiang, Chuhan
Graphical abstract: Highlights: Willis covered stent can achieved an satisfying complete occlusion rate for internal carotid artery aneurysms. Procedure-related hemorrhagic and ischemic complications are not higher than other series with Willis covered stent. Stent navigation failure, endoleak, and balloon occlusion test before procedure are not negligible. Abstract: The purpose of this study was to retrospectively analyse the clinical and angiographic outcomes of Willis covered stent placement for unruptured aneurysms in internal carotid artery. Forty-six consecutive patients with internal carotid artery aneurysms (49 cases) were included to evaluate clinical and angiographic outcomes. Covered stent placement was successful in 47 cases, whereas stent navigation failed in 2 cases. Of the 49 aneurysms (mean aneurysm size, 7.9 mm), 5, 6, and 38 were located in the petrous, cavernous, and ophthalmic segments, respectively. Immediate angiography revealed complete aneurysm exclusion in 36 (76.6%) cases, whereas minimal endoleak was observed in 11 cases. Four patients had procedure-related complications, including 1 patient with acute in-stent thrombosis, 2 with a post-operative subarachnoid haemorrhage, and 1 with artery rupture. Angiographic and clinical follow-up was available for 36 patients (38 aneurysms). Complete aneurysm occlusion was achieved in 34 (89.5%) cases, endoleak was present in 2 cases, and aneurysm recurrence occurred in 2 cases. Asymptomatic in-stent stenosis was observed in 3 patients. No hemorrhagic or ischemic events occurred during the follow-up period. At follow-up, the modified Rankin scores were 0–2 for 35 patients and >2 for 1 patient. Satisfactory angiographic outcomes were achieved in our study. However, the risks of stent navigation failure, endoleak after balloon re-inflation, procedure-related complications and coverage of side branches should be considered when choosing the best therapeutic option for internal carotid artery aneurysms.